2010
DOI: 10.1128/jvi.01510-09
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Associates with the Human Cytomegalovirus DNA Polymerase Accessory Subunit UL44 and Is Necessary for Efficient Viral Replication

Abstract: In the eukaryotic cell, DNA replication entails the interaction of multiple proteins with the DNA polymerase processivity factor PCNA. As the structure of the presumptive human cytomegalovirus (HCMV) DNA polymerase processivity factor UL44 is highly homologous to that of PCNA, we hypothesized that UL44 also interacts with numerous proteins. To investigate this possibility, recombinant HCMV expressing FLAG-tagged UL44 was generated and used to immunoprecipitate UL44 and associated proteins from infected cell ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
112
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(126 citation statements)
references
References 60 publications
(63 reference statements)
11
112
2
1
Order By: Relevance
“…The UL44 protein is structurally homologous to the eukaryotic proliferating cell nuclear antigen (PCNA), which interacts with multiple proteins (31). Recent proteomic analyses demonstrated that the UL44 protein interacts with a variety of proteins, including transcription factors other than viral replication-related proteins (13,(45)(46)(47). Therefore, it is conceivable that pre-RCs including UL44 protein act to optimize the timing of late gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The UL44 protein is structurally homologous to the eukaryotic proliferating cell nuclear antigen (PCNA), which interacts with multiple proteins (31). Recent proteomic analyses demonstrated that the UL44 protein interacts with a variety of proteins, including transcription factors other than viral replication-related proteins (13,(45)(46)(47). Therefore, it is conceivable that pre-RCs including UL44 protein act to optimize the timing of late gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, nucleolin is required for both proper nuclear and subnuclear localization of HCMV replication compartment proteins. Furthermore, it is possible that, in infected cells, nucleolin, UL44, UL84 and either IRS1 or TRS1 interact within a large multiprotein complex (Strang et al, 2010a, b). Therefore, nucleolin may have an effect on the localization of both IRS1 and TRS1 in the infected cell.…”
Section: Introductionmentioning
confidence: 99%
“…UL44 could play a similar role and bind multiple proteins in replication compartments. Proteomic studies have indicated that UL44 associates with viral and cellular proteins found in replication compartments, including UL84 (Strang et al, 2010a). The binding of proteins to UL44 is increasingly well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations